Therapeutic responses to antibacterial drugs in vivax malaria. - Pukrittayakamee, S; Clemens, R; Chantra, A; Nontprasert, A; Luknam, T; Looareesuwan, S; White, N (2001)
Some antibacterial drugs have antimalarial activity that can be exploited for the prevention or treatment of malaria. Monotherapy with tetracycline, doxycycline, clindamycin or azithromycin was assessed in 1995-98 in 92 adult patients in Thailand with Plasmodium vivax malaria. All patients recovered following treatment and the early therapeutic responses were similar among the 4 groups. The overall median fever clearance time was 57 h and the mean (SD) overall time to parasite clearance was 134 (48) h. Of 66 patients who completed a 28-day follow-up, reappearances of vivax infection occurred in 27 patients (41%) from all groups; delayed appearances of falciparum malaria occurred in 6 patients (9%), only from the azithromycin group. The overall mean (SD) time to reappearance of P. vivax was 23 (5) days and time taken for detection of falciparum malaria was 13 (4) days after starting treatment for vivax malaria. The 28-day cumulative cure rates of clindamycin (n = 12), tetracycline (n = 18) and doxycycline (n = 18) groups were similar (P > or = 0.14) and all were significantly higher compared to the azithromycin group (n = 18; P < or = 0.04). The intervals until vivax reappearance were also significantly shorter in the azithromycin group [mean (SD) = 21 (6) vs 25 (3) days, P < 0.05] suggesting that some of these were recrudescences. The apparent success rate (no subsequent appearances of either vivax or falciparum infection) was significantly lower for the azithromycin group (11%) compared to the other groups (34-78%; P < 0.01). In current antibacterial treatment regimens, short-course azithromycin has inferior antimalarial activity compared to clindamycin or the tetracyclines.